PERAN UNITED NATION CHILDREN'S FUND (UNICEF) DALAM MENANGANI KASUS PERDAGANGAN ANAK DI INDONESIA PERIODE 2017-2019 - Anissa Rizkia Putri Wikarsa (2020)
The issue of child trafficking is an issue of child rights violations that have not been completed in various countries, including Indonesia. Indonesia is a country with many borders with other countries, which makes it even easier for child trafficking crimes. This trade crime reached a fairly high number and moved dynamically in 2017-2019. This issue makes UNICEF as an international organization addressing the issues about the child, to perform its role. UNICEF assists the Indonesian government through the NPAs program and the implementation of the Children's Rights Convention into Indonesia's law. This research approach is using qualitative, the type of research used is descriptive analysis. The sources used are secondary data data obtained from the official site of the institution concerned with the issues studied, namely KPAI and UNICEF, and through the study of the library. The data will be analyzed using role theory, international organization theory and Human Trafficking concept. Based on the analysis data done, the conclusion that UNICEF as an international organization addressing the issues about the child has been performing its role by assisting the Government of Indonesia in addressing the trafficking of children in Indonesia through established programmes.